2020
DOI: 10.2147/rmhp.s248222
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anticoagulation Control of Warfarin in Pharmacist-Led Clinics Versus Physician-Led Clinics: A Prospective Observational Study</p>

Abstract: Purpose: Warfarin is an affordable drug used for numerous indications, and still a favorable choice for patients with a history of bleeding from direct oral anticoagulants or presence of valvular heart diseases. However, warfarin requires regular international normalized ratio (INR) monitoring for safety and efficacy. Warfarin's efficacy and safety is correlated with actual time spent within the therapeutic INR. Time in therapeutic range (TTR) is an estimate that measures the percentage of actual time spent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…A Saudi prospective observational study compared pharmacists led versus physician led anticoagulation clinic, included 62 patients showed consistent findings to our study despite a smaller sample size ( Alghadeeer et al 2020 ). TTR levels were statistically higher among patients in pharmacist-led than the physician-led clinic (87.27%±3.82% and 52.48%±5.49%, respectively; p < 0.001).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A Saudi prospective observational study compared pharmacists led versus physician led anticoagulation clinic, included 62 patients showed consistent findings to our study despite a smaller sample size ( Alghadeeer et al 2020 ). TTR levels were statistically higher among patients in pharmacist-led than the physician-led clinic (87.27%±3.82% and 52.48%±5.49%, respectively; p < 0.001).…”
Section: Discussionsupporting
confidence: 86%
“…For 27 patients followed retrospectively by physicians and prospectively by clinical pharmacists, TTR was statistically higher during clinical pharmacists’ care (91.70% ±2.93% versus 61.39%±5.11%, respectively; p < 0.001). ( Alghadeeer et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1432 studies were found, but only studies that evaluated the impact of ambulatory care clinical pharmacists on patients' outcomes were included (Table 2). 11‐22 …”
Section: Methodsmentioning
confidence: 99%
“…Currently, in KSA, several well‐established ambulatory care pharmacy clinics specialize in medication therapy management (MTM), anticoagulation, and diabetes, all of which have been proven to enhance clinical patient outcomes and patient satisfaction 11‐22 . A review of these clinics is presented in (Table 2).…”
Section: Methodsmentioning
confidence: 99%